The role wills and estate planning played in Anne Lister's life1. Issue 4 (18th November 2022) - Burda, Joan M.
Abstract: Anne Lister became the owner of Shibden Hall in Halifax in 1826, when her Uncle, James Lister, died. Inheriting Shibden was the culmination of a campaign Anne Lister began as a young woman. Lister's journals reflect her thoughts concerning the actions she took to convince her uncle that she was the best choice to ensure that the Shibden estate remained in the Lister family and how she provided for Ann Walker after their commitment in 1834. The journal entries provide an insider's view of the process she engaged in to accomplish her goals. This paper will discuss the wills Anne Lister (1791–1840) and Ann Walker used in preparing for the disposition of their respective estates following their deaths. Lister used wills and other estate planning measures to protect herself and provide for others. The paper also discusses the shortcomings and missed opportunities for adequate legal advice given to Miss Lister and Miss Walker by their lawyer, his failure to consider and advise on the situations that did occur after Lister's death. Anne Lister was prolific in her instructions to her lawyer about her will, but she did not think of everything. The paper also includes a brief background on English law concerning wills, inheritance, and women's rights evolved over many centuries. Considering the various legal aspects of common law and statutes concerning who could inherit under English law, and the restrictions that existed if an owner died intestate, provide a necessary overview of the importance of planning ahead.